MEMBANGUN SUMBER DAYA MANUSIA YANG SEHAT DAN BERKARAKTER - Nurul Kusnah (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2017)
Development was a word we often hear so pragmatic, yet in reality it is not. Development was not only about the availability of infrastructure, buildings and facilities, economic growth and life expectancy. Development was not merely statistics and figures in the balance sheet. Covering all aspects of development where there are opportunities for every individual to flourish with dignity in the face of a changing world. Education was the main thing for the people after basic needs. However, it took a nation's education is education that is fair to everyone both in the physical, psychological and spiritual. In Article 3 of the Law on National Education System stated that the national education serves to develop the ability and character development and civilization dignified nation in the context of the intellectual life of the nation, is aimed at developing students' potentials to become a man of faith and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and accountable.